The White House world : transitions, organization, and office operations - Kumar, Martha Joynt; Sullivan, Terry (Terry O.) (Presidency and leadership, 2003)
When George W. Bush and his staff finally got word he had officially won the 2000 presidential election, they had only thirty-seven days left to shift from campaign mode to governing. Fortunately for the Bush team, a group of presidency scholars had gathered and provided them with a wealth of substantive analysis about presidential transitions and White House operations. With information covering six administrations and interviews with seventy-five former senior White House officials as well as with President Gerald Ford, the White House Interview Program proved an important resource for the new occupants of the West Wing. The White House World gathers and digests the same material that was provided to the incoming White House staff. Its individual chapters contain a veritable "how to" manual: information on the dynamics of White House operations; the functions of seven critical White House offices; and the actual transition of President Bush. In a final section, scholars and Bush administration insiders offer brief views of George W. Bush's unique transition into office. In addition to Kumar and Sullivan, scholars contributing to the volume include: Peri E. Arnold, MaryAnne Borrelli, John P. Burke, George C. Edwards III, John Fortier, Karen Hult, Nancy Kassop, John H. Kessel, G. Calvin Mackenzie, Norman Ornstein, Bradley H. Patterson, Jr., James P. Pfiffner, Kathryn Dunn Tenpas, Charles Walcott, Shirley Anne Warshaw, and Stephen J. Wayne. The section on the Bush transition also contains an essay by Clay Johnson, executive director of the Bush-Cheney Transition and now director of the White House Office of Presidential Personnel. The project was sponsored by the Pew Charitable Trustsand carried out by members of the Presidency Research Group of the American Political Science Association. This is a must-have book for all current and aspiring participants and all serious observers of the American presidency